Assessment of diabetic retinopathy in type 1 diabetes in a diabetes care center in South India-Feasibility and awareness improvement study - Rajalakshmi, Ramachandran; Shanthirani, Coimbatore Subramaniam; Anandakumar, Amutha; Anjana, Ranjit Mohan; Murthy, G V S; Gilbert, Clare; Mohan, Viswanathan (Indian journal of ophthalmology, 2020)
The prevalence of youth-onset diabetes, both type 1 diabetes (T1D) and young-onset type 2 diabetes (YT2D) are gradually increasing in India. Early and repetitive screening for diabetic retinopathy (DR) is essential to provide timely management, and thereby prevent visual impairment due to the silent sight-threatening microvascular complication of diabetes. A study was undertaken at a diabetes care center in Chennai, south India, to assess the feasibility of screening for DR in T1D in a diabetes clinic and determine the burden of sight-threatening DR (STDR) in individuals with T1D. 315 people with T1D were screened for DR (mean age at onset of diabetes 12.3 ± 6.4 years) by digital retinal color photography, at the urban diabetes center, in a semi-urban and rural diabetes clinic. Counseling about diabetes and the importance of annual screening for retinopathy was provided by diabetes educators. Participants were reviewed after 6 months/1 year based on ophthalmologist's advice. DR was detected in 37.1% (n = 117), 42 (13%) of whom had STDR.Three-quarter participants were compliant with the annual follow-up retinal examination. The peer support group was established for participants with T1D and their families to foster interactions with service providers. The peer group meetings helped to increase the awareness of retinopathy among the parents and individuals with T1D. This narrative provides details of the study that shows that screening for DR among individuals with T1D in a diabetes clinic is a feasible model, irrespective of its location.